Effect of Growth hormone gene polymorphisms (T3094C) SNP on productive and physiological performance in Hubbard broiler chicken - abidalraheem, Ali; AL-kreem, I.Q (Journal of Kerbala for Agricultural Sciences, 2018)
In this study commercial broiler hybrid (Hubbard) was used to detect the T3094C SNP in the fourth intron of chicken GH gene and investigate its effect on the productive and physiological performance in broiler chicken. PCR- RFLP method was used to identify this SNP. The results revealed that three genotypes were found when using of Msp1 restriction enzyme wild genotype TT, heterozygous TC and mutant CC. Highly significant difference (p<0.01) was found between the distribution of the different genotypes, the genotype TT had the highest percentage followed by TC then CC, allele T had the superiority over allele C, also significant differences (p<0.05) were found in mean of the weekly live body weight and weekly weight gain at 4, 5 and 6 weeks of age, and there was significant effect (p<0.05) of the T3094C SNP on the mean of carcass weight and relative weight of thighs between the different genotypes, the T3094C SNP was affect significantly (p<0.05) on the mean of blood serum total protein concentration at 14 days of age and on the mean of blood serum total protein and glucose concentration at 42 days of age .